Primary anorexia nervosa (weight phobia) in males. - Hasan, M. K. (BMJ Group, 1977)
Ten cases of primary anorexia nervosa (weight phobia) in males (as against 196 females) have been treated in the United Birmingham Hospitals over 19 years. A discrete syndromes appears to exist with much to support the view that it is the counterpart of primary anorexia nervosa in the female. Six illustrative case histories are described briefly. The heavy loading with consistent abnormalities of psychiatric interest makes it very probable that weight phobia is primarily a psychiatric disorder.